Kemanfaatan Hukum “Peran Pejabat Pembuat Akta Tanah” Dalam Upaya “Peralihan Hak Tanah Ulayat” oleh “Anggota Masyarakat Adat” Daerah Pora Nusa Tenggara Timur - Melfijanti Melfi; M. Ryan Bakry; Frengki Hardian (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The position of indigenous peoples is basically recognized by the Indonesian nation with diversity in Indonesia which is a reflection of Bhinneka Tunggal Ika and also this recognition is contained in the amendment to the basic law "1945 article 18B paragraph 2 and article 28I paragraph 3". Indigenous peoples are marginalized due to their lives that still adhere to the prevailing customs and customary law system. So that with the marginal position of indigenous peoples, they feel unprotected by the state even though there is regulatory recognition of them. This recognition is not limited to the community alone, but also overall recognition for their sustainability, especially in efforts to recognize customary land. Customary land is land that is jointly owned by the indigenous community. Disputes about customary land still occur due to intervention from the government and entrepreneurs to be able to make customary land as state land. Based on the description above, the formulation of this problem aims to determine the role of related agencies on land assisted by "Notaries and Land Deed Officials (PPAT)" regarding the "transfer of rights" of customary land, as well as legal benefits that can be felt by indigenous peoples of the Pora region of East Nusa Tenggara with the existence of Land Office agencies, Notaries and Land Deed Officials (PPAT). The research method used is Normative empirical which is sourced from laws and regulations and approaches to the case, namely indigenous peoples in the Pora area. Research area Pora East Nusa Tenggara. That there is no regulation made by the government to protect indigenous peoples and their customary rights, namely customary land. So it is hoped that the existence of government regulations on the Pora area will be able to provide recognition for indigenous peoples in the form of recognition and customary rights, customary land in the Pora area of East Nusa Tenggara.